Beginners’ Learning Experiences in Qualitative Research: Inputs for Curriculum Enhancement of Senior High School in Practical Research - Friales, Wilter (JPAIR Institutional Research, 2019)
‘Beginner Researchers’ refer to the Senior High School Students learning Qualitative Research for the first time. Qualitative Research is one of the Applied Track subjects offered for the SHS and is deemed relatively new for the students. This study aimed to describe the experiences of beginner researchers on learning Qualitative Research. Specifically, on the questions: How they find learning Qualitative Research for the first time; their learning strategies; teachers mentoring styles as experienced by them; Learners’ collaboration and leadership; their challenges and the implications to the teaching and learning process. This study utilized Descriptive Qualitative Research as a research design. There were two sets of focused group discussions conducted one group with eight participants and the other group with six participants during the actual interview. 'Beginner researchers’ view Qualitative Research as a rigorous process that requires good communication and social skill; a difficult subject; provides new knowledge and experiences; and interesting subject. Repetitive teaching and the prompt feedback mechanisms on students’ output were teacher’s mentoring strategies while learning together as co-learners; Learners’ collaboration; and delegation of tasks were the identified concepts on learners learning strategies. The challenges of the beginner research were on the group dynamics and the methodology’s technicality. The results implied reviewing the curriculum on Practical Research Subject and contextualized the process based on the actual needs of the students based on how it has been delivered for the past years of the Senior High School implementation;
Keywords: Education; Inputs in Curriculum Enhancement; Practical Research; Descriptive Qualitative Research; Philippines